Effect of Sin Tax on Electronic Cigarette Consumption in Quezon City - Elizabeth Andrade; Nat Daniel Garcia; Dylan Kurt Valbuena; Marie Antoinette Rosete (Faculty of Science and Technology University of Pramita Indonesia, 2023)
Electronic nicotine-containing electronic apportioning frameworks, commonly known as electronic cigarettes, have been predominantly considered a less damaging elective to standard cigarette smoking. E-industries have rapidly expanded, utilizing intense advancing messages comparable to those used to progress cigarettes in decades. Moreover, e-cigarettes are more engaging than conventional cigarettes for various reasons: tallying the choice of distinctive flavors, ease of availability, and utilization and effect of media. In accordance with this, the implication of sin tax towards e-cigarettes is to define sin tax as exacted on particular merchandise and administrations when purchasing the goods or products. These things get the extract assessment due to their capacity, or discernment, to be destructive or expensive to society. The study aims to determine the effect of the sin tax on e-cigarette consumption in Quezon City. The descriptive-quantitative will be imposed in the study as it involves data collection that is relevant to answering the concern of the subject of the study. The researchers will use a snowball sampling technique to reach the target sample size of 385. This method relies on recommendations from individuals with a specific interest characteristic with the target population. Identifying relevant literature will lead to the development of a self-made questionnaire. Thus, a pilot study will be conducted among 30 UST students to show the validity and reliability of the questionnaire. Using statistical software, a priori power analysis will be used to find the effect size given alpha. Moreover, the researchers will comply with the data privacy act law of 2013 and will ensure the commentary of the university's ethics and research review committee.